Incidence of persistent/late chronic anemia in newly diagnosed patients with chronic myeloid leukemia responsive to imatinib. Issue 2 (19th November 2014) - Latagliata, Roberto; Volpicelli, Paola; Breccia, Massimo; Vozella, Federico; Romano, Angela; Montagna, Chiara; Molica, Matteo; Finsinger, Paola; Carmosino, Ida; Serrao, Alessandra; Zacheo, Irene; Santopietro, Michelina; et al.
<x xml:space="preserve">Abstract</x> In patients with chronic myeloid leukemia (CML) responsive to imatinib, it is still unknown whether the long‐lasting treatment could induce the appearance of a persistent/late chronic anemia. To highlight this issue, we revised 128 patients with CML (M/F 64/64, median age at diagnosis 56.9 years, interquartile range 43.0–69.3) treated at our Institution with 1st line imatinib for at least 36 months and in stable complete cytogenetic response. At the 36th month of imatinib, a chronic anemia (Hb < 12 g/dl for > 6 months) was present in 38/128 patients (29.6%): the anemia was moderate (Hb > 8 ≤ 10 g/dl) in 12 patients (9.3%) and mild (Hb > 10 < 12 g/dl) in 26 patients (20.3%). All patients with persistent/late chronic anemia had a low reticulocyte count and 8/38 a condition of iron deficiency without clinical and instrumental signs of chronic blood loss. Four out of 38 patients (10.5%) needed red cell transfusions during the follow‐up. At a landmark analysis from the 36th month of imatinib treatment, cumulative 4‐year overall survival (OS) for patients with chronic anemia was 94.4% (CI 95% 83.8–100) compared to 93.5% (CI 95% 87.2–99.8) for patients without chronic anemia (P = 0.617). In conclusion, the occurrence of a late chronic anemia during long‐lasting treatment with imatinib has been observed in about 30% of our responsive patients: its occurrence does not seem to affect OS, but its real impact should be evaluated on a larger cohort of patients. Am. J. Hematol. 90:105–108, 2015. © 2014 Wiley Periodicals, Inc.